Broadband dielectric characterization of piezoelectric poly(vinylidene fluoride)thin films between 278 K and 308 K - Ciocci Brazzano, Ligia (2013)
This work describes the dielectric properties of piezoelectric poly(vinylidene fluoride) (PVDF) thin films in the frequency and temperature ranges relevant for usual applications. We measured the isothermal dielectric relaxation spectra of commercial piezoelectric PVDF thin films between 10 Hz to 10 MHz, at several temperatures from 278 K to 308 K. Measurements were made for samples in mechanically free and clamped conditions, in the direction of the poling field (perpendicular to the film). We found that the imaginary part of the dielectric relaxation spectra of free and clamped PVDF samples is dominated by a peak, above 100 kHz, that can be characterized by a Havriliak-Negami function. The characteristic time follows an Arrhenius dependence on temperature. Moreover, the spectra of the free PVDF samples show two additional peaks at low frequencies which are associated with mechanical relaxation processes. Our results are important for the characterization of piezoelectric PVDF, particularly after the stretching and poling processes in thin films, and for the design and characterization of a broad range of ultrasonic transducers.